Knowledge and Discernment: Reflections on the Integration of Biblical Studies and Spirituality - Leslie T. Hardin (Religions)
In the introduction to The Violence of the Lamb: Martyrs as Agents of Divine Judgment in the Book of Revelation, Paul Middleton recounts that at the 2008 annual meeting of the Society of Biblical Literature, he was asked about the possible connections between John’s letters to the seven churches of Asia and modern ecclesiastical practice [...]